Konstruksi Pendidikan Reproduksi Bagi Remaja dalam Bingkai Pendidikan Islam - Ahmad Sulton (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2021)
Adolescents are an age that is prone to deviations in sexual behavior. Sex education is very important for adolescents to be able to understand themselves and their sexuality. Many things cause children in adolescence to commit sexual deviations or free sex as a way of escape from various problems and a lack of children’s ability to control themselves from their emotions. Sex education covers several aspects of life, consisting of Anatomy of the body, health, personal hygiene, reproductive system, human relations, sexual response, religion, and expressions of love. According to Islam, sex education is to educate lust in accordance with the teachings of Islam, so that it becomes a lust blessed by God, in order to create an atmosphere of calm and happiness in the home, a place to educate offspring who obey God and to find out adultery. This study is categorized as library research. This type of study is qualitative research. It is called qualitative because this study emphasizes the process, especially the process of obtaining information related to the title of the study, namely the construction of sex education for adolescents' perspective Islamic education. This study aims to understand sex education (reproduction) for adolescents from the perspective of Islamic education so that it can be expected to reduce sexual deviant behavior